(3JPcQI GdYdeGA hGdTYQGAs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , hUdi hSde Ydi SjOfG eMeO CaVd Ndbg IYdi Bdg hUMHg hSde (B((3bGd(B) (3eGHK TchGg dhdG eSg GdCde hdG JChg dhdG Tag GdSbe s
(3BNQgG (B:s
(3abGd (B:(3Cf GdfHi Udi Gddg Ydjg hSde Mjf LdS Ydi GdQahf GdCNVQ hGfJgi Edi Cf SeY UQja GdCbdGe de jcf CbQH Edi Gddg ef jhfS ai HWf GdMhJ ai XdeI GdHMQ hGddg Gdehab s
(3hgh eLehYI ai JQGLe cKjQ ef GdYdeGA hGdTYQGA hPcQ cKjQ ef CTYGQYe ef SfI (B365 (3g Edi efJUa GdbQf GdKGef GdgLQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B171 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3Yf GdeJMa GdHQjWGfi(B) (9909) s
Keywords: (3GdCOHs